The Effect of Product Quality, Word of Mouth, and an Event on Consumer Decisions to Buy Batik Gonggong in Batam City - Ebta Taurusia; Theresia Pradiani; Fathorrahman Fathorrahman (Journal of Social Research, 2023)
In the business world, there is a competition to win the hearts of consumers. Creasingly difficult business competition demands businesspeople to maximize their performance, especially in the field of fashion products especially the Batik Gonggong typical of Batam City. One of the challenges is how to create purchasing decisions for Gonggong batik products so that customers want to keep using them instead of switching to other products. The purpose of this study was to analyze the influence of product quality, word of mouth, and events on consumer decisions to buy Batik Gonggong in Batam City. This research uses quantitative methods. The sampling method used was nonprobability sampling with a purposive sampling technique, namely consumers who purchased batik Gonggong. The sample or respondents in this study were 100 people from Batam City, and the data was collected using a questionnaire. The data was analyzed using the classical assumption test, multiple linear regression, and hypothesis testing, specifically the coefficient of determination, the t-test, and the f-test. The results of the research partially concluded that 1) Product quality has a significant effect on consumer buying decisions, 2) Word of mouth has a significant effect on consumer buying decisions, 3) Events have a significant effect on consumer buying decisions, and simultaneously conclude that 4) product quality, word of mouth, and events influence purchasing decisions.